Determinants of Financial Management Behavior in MSME Actors in West Bandung Lembang District - Agus Kusmana; Syarif Ali (Garuda Prestasi Nusantara Consulting, 2023)
This study aims to determine the effect of Financial Literacy, Education Level and Income on Financial Management Behavior in micro, small and medium enterprises (MSMEs in Lembang West Bandung District. This research is a quantitative study. This study uses MSME actors in West Bandung Lembang District as the population. The method used is probability sampling, especially simple random sampling with a sample size of 90 respondents. Data collection was carried out by distributing questionnaires. The analysis technique used is the PLS (Partial Least Square) analysis method. The results of this study indicate that Financial Literacy, Education Level and Income have a significant influence on financial management behavior. Keywords: Financial Literacy, Education Level, and Income